Cooperation in computer software development. - Li Ning (Beijing Review, 1996)
The China Software Industry Association (CSIA) and the world-famous Intel have revealed that a new generation of multimedia computer software with distinctive Chinese characteristics will soon be available to consumers. The software, which will be manufactured by CSIA and the Intel Software Architecture Development (Shanghai) Co. Ltd., will be provided to consumers along with purchases of personal computers. Marketing of the software will focus on package sales created to preserve intellectual property rights. The new product will be the first personal computer software package in China that will be fully compatible with domestically manufactured processing systems.